Mengkaji Tradisi Upacara Joka Ju Terhadap Ketentraman Masyarakat Wolopau Desa Wiwipemo Kecamatan Wolojita Kabupaten Ende Nusa Tenggara Timur - Nanik Ida Rosini (Journal on Education, 2023)
The purpose of this study was to determine the process of implementing the Jokhaju ritual tradition and the meaning of the Jokhaju ritual process in Wolopau Village, Wiwipemo Village, Wollojita District in the final period of the district. The research topic used by the author is the public figure Wolopau. The research method used by the author is a qualitative and descriptive approach. The method of data collection uses the interview method. The findings show that the Strengthening Rejection Ceremony (Jokaju) conducted by the Wolopau community in Wiwipemo Village, Wollojita District, Ende Regency has several stages, namely Peinel, Pana Manu, Koe Kol and Tagaau which are the uniqueness of the Volopau community. Where the purpose of this ritual is to drive away evil spirits from the village and thank you for the harvest.